Partnership Model in School Entrepreneurship Development - Diah Isnaini Asiati; Yudha Mahrom; Muhammad Asif Khan; Oscar Agyemang Opoku; Emi Puspita Sari (Journal of Management Studies and Development, 2022)
Entrepreneurship becomes an integral program for planning the progress of a country. The development of this program then becomes the responsibility of all parties, educational institutions, the government and the public. Educational institutions today, almost in all disciplines, seem to consider entrepreneurship as one of the learning programs. Vocational high school is one of the formal educational institutions designed to develop this program for its students. Various entrepreneurial models are tried to be developed to encourage further students' interest in developing entrepreneurship programs. Therefore, this study examines the partnership model in entrepreneurship development at Muhammadiyah vocational schools in Palembang, Indonesia. The study sample was 258 students from all Muhammadiyah vocational schools. The required data is primary, with a questionnaire as a data collection tool. The analyses used were factor analysis and regression. The results of the factor analysis extracted from all the indicators used gave rise to three variables that influence the decisions of entrepreneurial students, namely motivation, learning and perception. As for regression testing, only motivation and knowledge significantly affect entrepreneurial decisions, while perception has a significant effect.